2018
DOI: 10.1002/hed.25592
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of thyroxine replacement following hemithyroidectomy in a south east Asian cohort

Abstract: Background Thyroxine replacement following a hemithyroidectomy is not commonly discussed during consent for the procedure as the risk of hypothyroidism is perceived to be low. Methods Retrospective review of 901 patients who underwent hemithyroidectomy at a tertiary referral institution during the period January 2000 to December 2015. The main outcome studied was the overall incidence of hypothyroidism and the associated risk factors. Results Hypothyroidism developed in 123 (13%) patients and 94 patients (10%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In this study, we separately evaluated patients with subclinical hypothyroidism; this subgroup has not been adequately assessed in previous studies [ 19 , 20 ]. In our sample, 25% of patients with subclinical hypothyroidism following hemithyroidectomy reverted to euthyroidism without TH replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we separately evaluated patients with subclinical hypothyroidism; this subgroup has not been adequately assessed in previous studies [ 19 , 20 ]. In our sample, 25% of patients with subclinical hypothyroidism following hemithyroidectomy reverted to euthyroidism without TH replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Histological HT, the most common autoimmune disease ( 27 ), was the second predictor of postoperative hypothyroidism. Peng Ng et al ( 28 ) reported that HT was the only independent risk factor in a retrospective review of 901 patients. The presence of thyroid antibodies was found to be a significant factor by univariate analysis but did not maintain independence as a factor for postoperative hypothyroidism by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these studies reported that postoperative hypothyroidism is mostly subclinical, and that patients recover spontaneously, in many cases. Relatively well-known risk factors for postoperative hypothyroidism have been mentioned, such as preoperative TSH level, thyroiditis, and anti-thyroid peroxidase (TPO) antibody (3)(4)(5)(6)(7).…”
Section: Original Articlementioning
confidence: 99%